Bridging the Technological Divide : Technology Adoption by Firms in Developing Countries - Cirera, Xavier (Washington, DC: World Bank, 2022)
Many of the main problems facing developing countries today and tomorrow--growth, poverty reduction, inequality, food insecurity, job creation, recovery from the COVID-19 pandemic, and adjustment to climate change--hinge on adopting better technology, a key driver of economic development. Access to technology is not enough: firms have to adopt it. Yet it is precisely the uptake of technology that is lagging in many firms in developing countries.